Prenatal biochemical diagnosis of two forms of congenital diarrheal disorders (congenital chloride diarrhea and congenital sodium diarrhea): A series of 12 cases. (3rd January 2021) - Macraigne, Laure; Allaf, Bichr; Buffat, Christophe; Spaggiari, Emmanuel; Dimitrov, Georges; Fabre, Alexandre; Rosenblatt, Jonathan; Dreux, Sophie
Abstract: Objective: Congenital diarrheal disorders (CDDs) are a group of rare diseases among which some present as inherited disorders of intestinal electrolyte transportation: congenital chloride diarrhea (CCD) and congenital sodium diarrhea (CSD) with prenatal manifestations, mainly polyhydramnios, leading to premature delivery. Affected neonates present with watery stools, sometimes mistaken as urine, leading to a misdiagnosis of Bartter syndrome. The aim of this study was to study the value of a prenatal biochemical pattern in the case of suspected CDD. Methods: We retrospectively studied 12 amniotic fluids of CDD‐affected fetuses prenatally suspected and confirmed after birth. Digestive enzymes, proteins, and electrolytes were assayed and showed abnormal biochemical patterns. Results: The 12 infants (eight CCD‐ and four CSD‐affected) were born prematurely with a normal birth weight. Electrolytes and the Bartter index were normal for all cases. Amniotic fluid enzyme patterns were abnormal: anal leakage for nine, as expected, but vomiting of bile was observed for three infants, for whom an occlusive syndrome required surgery, and thereafter severe complications appeared with a poor prognosis. Conclusion: Amniotic fluid biochemical patterns differentiate CDD from Bartter syndrome. If a vomiting bile pattern is observed, postnatal management should take into account the hypothesis of a most severe complication. Key Points: What's already known about this topic? Congenital diarrheal disorders (CDDs) are a group of rare diseases that include CCD and CSD with perinatal manifestations as polyhydramnios, premature delivery and watery stools needing adapted neonatal care What does this study add? This study shows the value of an amniotic fluid biochemical pattern in differentiating CDD from Bartter syndrome for adapting postnatal management. A vomiting biochemical pattern is also a sign of potential most severe complication